Analisis Kelayakan Tarif Bus Trans Koetaradja Berdasarkan Ability To Pay (ATP) Koridor 2A Pusat Kota-Blang Bintang - Effendy, Amalia; Maulana, Ricky; Silviana, Mery (Tameh, 2024)
Since in 2018, Trans Koetaradja Urban Mass Transit is expected to provide maximum service to the community as users. Corridor 2A with the route Masjid Raya Baiturrahman-Lambaro-Blang Bintang. For now, the government applies full subsidies for bus users, meaning that bus users can ride this bus without paying. However, this condition will certainly not last forever. Calculation of the feasibility of bus fare based on Ability to pay is done to see the ability of this bus user to pay the bus fare. This study uses a Quantitative Descriptive Research Method through Survey Techniques involving 392 respondents to bus users given a survey form containing questions regarding: frequency of bus use, average monthly income and expenses and expenses to pay for transportation Respondents were selected based on activities, which were divided into 7 categories based on occupation, including: Students, Self-employed, Workers, Civil Servants, Non-workers and Housewives. The results of the questionnaire were then tabulated and calculated to see the distribution of ATP rates by considering income, percentage of expenditure on transportation and frequency of use. From the research results, the percentage of gender is 57% female and 43% male. The average frequency of use of the bus in 1 week is 4 times the transportation costs obtained range between Rp. 10,000 and Rp. 200,000 The average ATP value is Rp. 2,400.